A copper-zinc-superoxide dismutase (CuZnSOD) from redlip mullet, Liza haematocheila: Insights to its structural characteristics, immune responses, antioxidant activity, and potent antibacterial properties. (October 2021) - Sirisena, D.M.K.P.; Gayashani Sandamalika, W.M.; Neranjan Tharuka, M.D.; Madusanka, Rajamanthrilage Kasun; Jeong, Joon Bum; Lee, Jehee
Abstract: Copper–zinc superoxide dismutase (CuZnSOD) is a nuclear-encoded metalloenzyme responsible for scavenging harmful reactive oxygen species (ROS). In this study, the CuZnSOD homolog from redlip mullet ( Liza haematochelia ) (MuCuZnSOD) was structurally and functionally characterized to evaluate its antioxidant capacity, antibacterial properties, and protective level in various pathogenic stress conditions. Structural characteristics of MuCuZnSOD were evaluated using different bioinformatics tools. Pairwise sequence comparison and evolutionary tree structure revealed that the MuCuZnSOD sequence was closely related to the CuZnSOD sequence of Oplegnathus fasciatus with a 94.2% sequence identity. Sequence alignment analysis indicated that the CuZnSOD domain was well conserved. The highest transcriptional expression of MuCuZnSOD was identified in the blood. Immune challenge with lipopolysaccharide (LPS), Lactococcus garvieae, and polyinosinic-polycytidylic acid (poly I:C) exhibited an increased MuCuZnSOD mRNA expression in the blood and liver. Transfected green fluorescent protein-fused MuCuZnSOD was localized in the cytoplasm. Recombinant MuCuZnSOD (rMuCuZnSOD) was overexpressed in a bacterial system. The rMuCuZnSOD possessed significant antioxidant properties as determined by conventional xanthine oxidase assay. The optimum pH and temperature of rMuCuZnSOD were found to be pH 9 and 25 °C, respectively. rMuCuZnSOD enzyme activity increased in a concentration-dependent manner. Treatment with potassium cyanide highly inhibited the rMuCuZnSOD activity. rMuCuZnSOD possessed a significant peroxidation activity in the presence of HCO3 ˉ ions as demonstrated by the increased viability in cells treated with the enzyme in the presence of hydrogen peroxide. Antibacterial assays showed that rMuCuZnSOD had significant growth-inhibitory effects on both gram-positive and gram-negative bacteria. Collectively, our findings demonstrate that MuCuZnSOD is an essential antioxidant protein, which regulates the host defense mechanisms and innate immunity under oxidative stress. Highlights: CuZnSOD was identified from redlip mullet ( MuCuZnSOD ). Conventional xanthine oxidase (XOD) assay confirmed the antioxidant function of rMuCuZnSOD. Antibacterial activity assay showed the antibacterial activity of rMuCuZnSOD. MTT assay verified the peroxidation function of rMuCuZnSOD in the presence of HCO3ˉ. Transcriptional level of MuCuZnSOD was significantly modulated by different pathogenic stimulants.